Metallogeny of the Dagangou Au-Ag-Cu-Sb Deposit in the Eastern Kunlun Orogen, NW China: Constraints from Ore-Forming Fluid Geochemistry and S-H-O Isotopes - Liang Li; Haotian Liu; Changbing Wang; Fengyue Sun; Kai Zhang; Chengcheng You; Yonggang Sun; Shucheng Tan (Geofluids)
A study of ore-forming fluid geochemistry and S-H-O isotopes has been conducted to reveal the metallogeny of the Dagangou Au-Ag-Cu-Sb deposit, NW China. Three mineralization stages are identified within Dagangou, including ankerite-quartz-pyrite (Ank-Qz-Py), quartz-Au-sulfide (Qz-Au-Sul), and quartz-calcite (Qz-Cal) stages. Four types of primary fluid inclusions (FIs) and various fluid inclusion assemblages (FIAs) are identified by petrographic observations, including pure CO2, CO2-bearing, vapour-liquid and halite-bearing FIs, most of which are distributed randomly or along growth zones. Raman spectroscopy suggests that the fluid vapour is mainly H2O and CO2 with minor N2, CH4, and C2H6. The homogenization temperatures of primary FIs from the Ank-Qz-Py to Qz-Au-Sul to Qz-Cal stages are 208.7–313.4°C, 184.3–251.7°C, and 167.3–224.2°C, with salinities of 3.4–13.4 wt.%, 5.4–39.5 wt.% and 4.9–11.4 wt.% NaClequiv.. Sulfide S isotopes show a predominant source of sedimentary sulfur with minor magmatic sulfur, as evidenced by δ34S values of -1.4–5.1‰. The FI H-O isotopes reveal that the primary fluid was derived from magmatic waters mixed with minor sedimentary water (δD=−90.0 to -86.8‰, δ18OH2O=6.7–7.4‰) and then was significantly diluted by meteoric water in the Qz-Cal stage (δD=−97.2 to -95.7‰, δ18OH2O=3.9–4.3‰). Thus, the ore-forming fluid geochemistry and S-H-O isotopes indicate that fluid boiling occurred in the Qz-Au-Sul stage due to a pressure reduction from 85 MPa to 70 MPa, which led to the phase separation of fluid, loss of CO2, increase in residual fluid salinity, and formation of immiscible FIAs and halite-bearing FIs in the Qz-Au-Sul stage. This indicates a system moving away from a primary equilibrium, resulting in the deposition of metallic elements. The Dagangou Au-Ag-Cu-Sb deposit, therefore, is an orogenic gold-polymetallic deposit with a mesozonal depth of 5.9–7.5 km.